Por una legislación comprometida con la sostenibilidad turística. Información, formación y educación ambiental e investigación, factores a considerar - GARCÍA SAURA, Pilar Juana (Observatorio Medioambiental, 2010)
Tourism education and training, and environmental education as well as the divulging of research related to tourism are decisive issues for the tourism sector given that in this sector the assistance and services involved should be suitably defined and the complexity of the areas involved demands preparation at both a human and a professional level. Based on an analysis of these factors in our local Autonomous Community tourism legislation, a comparative study has been carried out on the situation with regard to the different Autonomous Communities in Spain. References to environmental education in regional tourism legislation are much more scarce than others related to tourism training or information. However, in general, there is an interest in improvement and innovation in the sector and this is manifest in each and every one of the General Tourism Laws analysed.